Health Professionals' Perceptions of a Pediatric Nutrition Support Program Led by a Clinical Dietitian at a Low-resource Hospital Setting in Malawi (P12-028-19). (13th June 2019) - Daniel, Allison; Chatenga, Humphrey; Chimera, Bernadette; Mbale, Emmie; Chisala, Mphatso; Borgstein, Eric; Langton, Josephine; Gonzalez, Carmen; Bandsma, Robert; Vresk, Laura
Abstract: Objectives: The first four dietitians graduated in Malawi in 2017, providing a new opportunity to build capacity to introduce nutrition support in an acute care setting. We designed and implemented a pediatric nutrition support program at Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi including the hiring of a local dietitian in August 2018. Upon introducing this program, we aimed to qualitatively assess perceptions around the nutrition support program from the perspective of health professionals at QECH. Methods: Qualitative interviews using a narrative research approach were undertaken to understand perceptions about the nutrition support program. Participants were selected through a purposive sampling approach across the eight wards within the nutrition support program at QECH. Interviews were held with nurses ( n  = 5) and clinicians and surgeons ( n  = 11) at QECH in November and December 2018. These interviews were audio-recorded before being transcribed and themes were then coded inductively using NVivo 11 software. Results: All participants of the qualitative interviews emphasized the importance and impact of the nutrition support program in enhancing care of hospitalized children and therefore improving child outcomes such as tolerability of clinical interventions, decreased duration of stay, and reduced risk of hospital readmission. Other themes that arose were the receptiveness of guardians of children who received nutrition support, the importance of engaging other health professionals in nutrition support, and the need for prioritization of nutrition support by the Ministry of Health to sustain and scale up this type of program in Malawi. Conclusions: Qualitative interviews with nurses, clinicians, and surgeons highlighted the value of nutrition support to improve quality of care in low-resource hospital settings. Integration of dietitians into the healthcare system in low- and middle-income countries like Malawi will require further advocacy around the potential for nutrition support to improve outcomes in vulnerable children. Funding Sources: The introduction of the nutrition support program was funded by the Centre for Global Child Health Catalyst Grant from the Hospital for Sick Children.